Adalimumab and sulfasalazine in alleviating sacroiliac and aortic inflammation detected in PET/CT in patients with axial spondyloarthritis: PETSPA - Juha‐Pekka Kaijasilta; Anne M. Kerola; Riitta Tuompo; Heikki Relas; Antti Loimaala; Hannu Koivu; Jukka Schildt; Tuomas Kerola; Kari Eklund; Markku J. Kauppi; Tuomo V. M. Nieminen (Immunity, Inflammation and Disease)
Abstract Aim Inflammatory signals in the sacroiliac (SI) joints and the aorta of patients with axial spondyloarthritis (axSpA) were graded by positron emission tomography/computed tomography (PET/CT) imaging before and after treatment with sulfasalazine (SSZ) or adalimumab (ADA). Methods Patients with axSpA, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) ≥ 4, were recruited. Disease‐modifying antirheumatic drug‐naïve patients started SSZ for 12 weeks, whereas those with prestudy treatment with or contraindication to SSZ commenced ADA for 16 weeks. In addition, those patients in the SSZ group with insufficient response commenced ADA for 16 weeks. 18F‐fluorodeoxyglucose PET/CT was performed after inclusion and after treatment with SSZ and ADA. Maximum standardized uptake value (SUVmax) was assessed for the aorta and the SI joints, and maximal target‐to‐blood‐pool ratio (TBRmax) only for the aorta. Results Among five SSZ patients, mean ± SD BASDAI was 4.7 ± 1.6 before and 3.5 ± 1.4 after treatment (p = .101). In 13 ADA patients, the BASDAI decreased from 5.4 ± 1.6 to 2.8 ± 2.2 (p < .001). Among the SSZ patients, SUVmax in SI joints decreased from 2.35 ± 0.55 to 1.51 ± 0.22 (−35.8%, p = .029). Aortic TBRmax decreased from 1.59 ± 0.43 to 1.26 ± 0.26 (−33.2%, p = .087). In the ADA patients, SUVmax in the SI joints was 1.92 ± 0.65 before and 1.88 ± 0.54 after treatment (−1.8%, p = .808) and TBRmax in the aorta 1.50 ± 0.60 before and 1.40 ± 0.26 after treatment (−6.7%, p = .485). Conclusions Our small open‐label study showed that SSZ may reduce PET‐CT‐detectable inflammation in the SI joints, with a trend towards a reduction in the aorta.